Epileptic focus localization based on resting state interictal MEG recordings is feasible irrespective of the presence or absence of spikes. Issue 4 (April 2015) - Krishnan, B.; Vlachos, I.; Wang, Z.I.; Mosher, J.; Najm, I.; Burgess, R.; Iasemidis, L.; Alexopoulos, A.V.
Highlights For the first time a connectivity-based analysis of MEG data is tested for epileptogenic focus localization in patients with neocortical epilepsy. MEG recordings from five patients with medically-intractable focal epilepsy undergoing presurgical evaluation for resection of candidate epileptic focus were analyzed. Proposed algorithm can localize the epileptogenic focus accurately even in patients with normal MRI (MRI-negative) or patients without interictal abnormalities on scalp EEG (EEG-negative) or MEG (MEG-negative).